Riverine flood risk reduction in the Western Cape: a case study of the Baths River - Durham, Caryn (Department of Environmental and Geographical Science, 2023)
Globally, floods are viewed as the most destructive of all naturally triggered disasters. This is indicated by reported flood losses that exceed one third of the estimated total cost associated with all disaster events triggered by natural hazards. Additionally, flood events account for two thirds of the global population affected by all naturally triggered disaster events.